THE IMPLEMENTATION OF INTERNATIONAL DISASTER RESPONSE LAWS TOWARDS INDONESIAN SOVEREIGNTY - Mohammad Hazyar Arumbinang (FH IH UMY 013, 2016)
In the last decade, the occurrences of natural and man-made disasters with devastating damage towards affected societies in Indonesia have intensified. The 2004 tsunami in Aceh, the 2009 earthquake in West Sumatra and the 2010 Mount Merapi volcanic eruption are the natural disaster with causing a severe destruction which is beyond the capacity of the host state. The international humanitarian assistance by international organizations and foreign non-governmental organizations needed due to help the host state. The International Federation of Red Cross and Red Crescent Societies initiated the International Disaster Response Law (IDRL) and in 2008, the UN General Assembly adopted three resolutions concerning it. In 2007, Indonesian Government enacted Law N0. 24 of 2007 on Disaster Management in responding it. This legal instrument as a legal basis for the international communities to help affected state during emergency disaster response. However, the sovereignty of host state must be respected in giving humanitarian assistance during the disaster response. Regardless of the severity of a disaster or the number of victims waiting to be rescued, state sovereignty cannot be superseded due to that reason. In fact, the international organizations and foreign non-governmental organization might be violating the Indonesian sovereignty when giving humanitarian assistance during disaster emergency response situation. The objective of the research is to know does the implementation of International Disaster Response Laws upon Indonesia give the opportunity to an international organization and foreign non-governmental organization during disaster emergency response violated the sovereignty of Indonesia. By using normative legal research with statute approach and case approach, the research found that the implementation of International Disaster Response Laws of Indonesia during the disaster emergency response clearly gives an opportunity for the international organization and foreign non-governmental organization to violated the sovereignty of Indonesia.